Efecto de tipos de fritura en los compuestos nutricionales, funcionales y la acrilamida de un Snack a base de salak (Salacca zalacca) - Velasco Martínez, Edison Paul (2023)
Fruits are a nutritionally contributing food in our daily diet, which is why it is becoming increasingly necessary to generate alternatives that improve and guarantee the health of consumers, for this the fruit Salak (Salacca zalacca) known as ancestral and medicinal food, is very useful in the preparation of a snack. The objective of this research is to determine the effect of two types of frying about the nutritional and functional compounds and the acrylamide production of a snack. The conventional and vacuum frying types were applied in the different treatments respectively, where obtained optimal values of the different study variables, such as: the water activity (0.28) that is obtained through vacuum frying, unlike conventional frying with 0.34; regarding humidity was obtained at 4.59% in vacuum frying and 6.62% in conventional frying, stating that, according to the specifications of the Regulations for this food, vacuum frying is the most appropriate for the production process of a snack, presenting the best characteristics, as well as fat (16.94%), fiber (4.39%), protein (1.6%), ash 4.56%), total phenols (746.81mg Ac.Galico /100g), Vitamin C (1441.47 ug/g) and antioxidants (387.74 umol trolox/100g), and it can even be deduced that vacuum frying saves energy and improves the characteristics of the final product.